The Influence of Social Media on Civic Engagement among Indonesian Millennials - Maulana, Aliv Jordan; Cakrabuana, Galih; Wilda (Generasi Sains Indonesia, 2025)
In the past two decades, social media has become a dominant arena influencing public opinion, political discourse, and civic engagement, especially among younger generations. In Indonesia, with over 200 million internet users, millennials are the most active in using social media for both entertainment and participation in civic life. This study explores how social media influences civic engagement among Indonesian millennials, emphasizing how online activities foster awareness, activism, and offline involvement. Using a mixed-methods approach, the research combines surveys of 250 millennials from major cities with qualitative interviews. Findings reveal that Instagram (82%), TikTok (76%), and Twitter (65%) are the most utilized platforms for civic expression. Popular online actions include hashtag campaigns (75%), petitions (68%), and crowdfunding (60%), though conversion into offline engagement remains moderate. Key obstacles are misinformation (72%), superficial participation (58%), and harassment (45%). However, frequent civic use of social media correlates positively with volunteering and protests. Overall, social media both democratizes access to civic participation and enhances political awareness, yet risks shallow engagement and polarization.